2021
DOI: 10.5765/jkacap.200033
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial Interpretation of a Teenager’s Suicide: Based on Krystal’s Death in Casual Vacancy

Abstract: It is hard to accumulate research data on adolescents' suicide, because friends and family of the suicide completers might be reluctant to share the experience. To overcome the lack of information on adolescent suicide victims, the authors examined the risk and protective factors for adolescents' suicide from a character in a novel. Methods: Krystal, an adolescent female in the novel The Casual Vacancy by Joanne Rowling, failed to overcome her unfortunate circumstances and committed suicide. The authors analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Many studies have focused on the relationship between self-harm and suicide. Suicidal thoughts and behaviors are more likely to follow self-injurious thoughts and behaviors [8,9]. Self-harm is a major risk factor for suicide, and researchers have found that suicide rates are significantly high in the first year after self-harm occurs [10].…”
mentioning
confidence: 99%
“…Many studies have focused on the relationship between self-harm and suicide. Suicidal thoughts and behaviors are more likely to follow self-injurious thoughts and behaviors [8,9]. Self-harm is a major risk factor for suicide, and researchers have found that suicide rates are significantly high in the first year after self-harm occurs [10].…”
mentioning
confidence: 99%